Могильник козацької доби на Середньому Дніпрі - Готун, І.А.; Петраускас, А.В. (Археологія і давня історія України, 2022)
Публікація вводить до наукового обігу матеріали дослідження кладовища козацької доби, частково розкопаного Північною експедицією Інституту археології НАН України у с. С тайки на узбережжі Канівського водосховища. Характеризуються особливості матеріальної та простежених за матеріальними рештками елементів духовної культури жителів пункту, залучаються результати опрацювання виявлених знахідок фахівцями-антропологами. In 2006, the Stayky team of the Northern Expedition of the Institute of Archaeology discovered the multi-layered settlements on the edge of the plateau north of the village and on the Dnieper islands opposite it and carried out the rescue excavations of the wellknown center including the various settlements and a Cossack cemetery. The materials of the settlement structure have already been published, as well as the exploration of the historical and cultural heritage of the settlement. The paper describes the results of research of the cemetery. During the campaign ca. 250 m2 of area with 26 burials made according to the canons of Christian rituals have been unearthed. They have no grave goods, except, probably, of burial 16, just below of which a coin blank or demonetized product and a silver Riga solid from the Baltic possessions of Sweden, minted in 1653 by Queen Christina, were found. The absence of other synchronous materials in the layers of the site allows to connect these finds not with the settlement structures but with the cemetery. And the single artifacts of previous ages, collected in two graves, belong to the surrounding layer. Despite the partial destruction of some burials by the quarry and the damage of shallow pits by further household activities it was observed that the skeletons laid supine with arms crossed on the chest or abdomen, although during skeletonization the arms could move to the pelvis and along the body. Certain deviations are noted in the position of the head and lower jaw in particular. The graves are 0.35—0.90 m deep, the deceased were directed with the head to the west with a slight deviation to the south, usually associated with the seasonal place of the Sun above the horizon. Gender and age differences have not been traced by the depth or direction of burials, although a higher concentration of graves, possibly a family plot, was found in one of the excavation area. Mutual overlaps of burials are few, although the damage of some graves with a moving of bones was observed. Processing of anthropological materials by specialists allowed to trace the peculiarities of ethnic features and physical development of the inhabitants of the site.